Formaldehyde barrier efficiency of melamine impregnated paper and melamine edge-banding tape surfaced particleboard and MDF - Medved, Sergej (Acta silvae et ligni, 2018)
Particleboard and MDF are the most usable materials for furniture production, where emission of formaldehyde should be as low as possible. In order to improve aesthetic properties of particleboard and MDF they are covered with appropriate surfacing material. In most cases, melamine impregnated paper is used for face layers. But covering faces should be accompanied with covered edges, as due to low density of core layer formaldehyde much more easily emits from edges than from faces. The presented research shows differences in formaldehyde emission rate at unsurfaced and surfaced MDF and particleboard. For face layer, melamine impregnated papers with grammages of 130 g/m2 and 200 g/m2 were used, while for covering edges, melamine edge-banding tape was applied. In the research it was determined that higher barrier effect was achieved when impregnated paper with a grammage of 200 g/m2 was used. When surface was completely covered with impregnated paper and melamine edge-band tape, formaldehyde emission was lowered by between 83 % and 94 %.
Keywords: emisija formaldehida; formaldehyde emission; iverna plošča; MDF; melamine edge band-tape; melamine impregnated paper; melaminski robni trak; oblaganje; papir impregniran z melaminsko smolo; particleboard; surfacing